(untitled) - Richards, Jack C (Cambridge, 2000)
New Interchange is a multi-level series for adult and young adult learners of English from the beginning to the high-intermediate level. The Workbook has six-page units that follow the same sequence as the Student's Book. It has interesting grammar, vocabulary, and writing activities, appropriate for classwork or homework. It also has numerous reading passages that recycle and review language from previous units
Keywords: English language,Communication, International